Bone char prepared by CO2 atmosphere: Preparation optimization and adsorption studies of Remazol Brilliant Blue R. (10th September 2017) - Bedin, Karen C.; de Azevedo, Stéfani P.; Leandro, Patricia K.T.; Cazetta, André L.; Almeida, Vitor C.
Abstract: We report the preparation of bone char from bovine bone using CO2 atmosphere at high temperature. Response surface methodology with a central composite rotatable design was applied to optimize the process parameters of temperature, time and CO2 flow. The significance and interaction of independent variables were tested by variance analysis and the experimental results showed that temperature and time were the significant factors on BET surface area with an antagonistic effect. The optimum conditions were found to be at temperature of 451 °C, time of 109 min and CO2 flow of 130 cm 3 min −1 . The bone char obtained from this optimized conditions showed a BET surface area of 137 m 2 g −1 and essentially mesoporous structure. This bone char was analyzed by scanning electron microscopy, Fourier transform infrared spectroscopy, pH PZC, X-ray diffraction and thermogravimetric analysis. Batch adsorption studies were performed with Remazol Brilliant Blue R (RBBR). Non-linear fits of Langmuir, Freundlich and Toth isotherm models and pseudo-first-order, pseudo-second-order and Elovich kinetic models to experimental data were investigated. The RBBR adsorption data onto bone char were well described by the Langmuir and Elovich models, indicating a monolayer adsorption ( q m = 20.6 mg g −1 ) on homogenous surface and chemisorption mechanism, respectively. Thermodynamic studies demonstrated that the adsorption process is endothermic and spontaneous. Graphical abstract: Highlights: Preparation conditions of bone char (BC) under CO2 atmosphere were investigated. Temperature and time were the significant factors for BET surface area ( S BET ). BC optimized (BCop ) have S BET of 137 m 2 g −1 and hydroxyapatite in its surface. BCop monolayer adsorption capacity was 20.6 mg g −1 for Remazol Brilliant Blue R.